Quality of Life in children with epilepsy - Dr. Roosy Aulakh (Pediatric Review: International Journal of Pediatric Research, 2018)
Care of children with epilepsy (CWE) in developing resource limited nations like India includes major emphasis on seizure control with minimal possible side effects of anti-epileptic drugs. Evaluation of QOL of CWE and steps to improve it is unfortunately not considered as an important issue.